A novel method for power quality multiple disturbance decomposition based on Independent Component Analysis - Lima, Marcelo A.A.; Cerqueira, Augusto S.; Coury, Denis V.; Duque, Carlos A. (International journal of electrical power & energy systems, 2012)
► We propose a method to decompose a power system signal into its isolated disturbances. ► We use Independent Component Analysis to separate disturbances occurring at same time. ► The method allows the decomposition when only a single measured signal is available. ► The performance is compared with that resulting from the Discrete Wavelet Transform. In this paper, a novel method for power quality signal decomposition is proposed based on Independent Component Analysis (ICA). This method aims to decompose the power system signal (voltage or current) into components that can provide more specific information about the different disturbances which are occurring simultaneously during a multiple disturbance situation. The ICA is originally a multichannel technique. However, the method proposes its use to blindly separate out disturbances existing in a single measured signal (single channel). Therefore, a preprocessing step for the ICA is proposed using a filter bank. The proposed method was applied to synthetic data, simulated data, as well as actual power system signals, showing a very good performance. A comparison with the decomposition provided by the Discrete Wavelet Transform shows that the proposed method presented better decoupling for the analyzed data.